Note preliminaire sur la faune de mollusques du canyon Viteaz - Glicherie, Caraivan; Lup, Ion (Cercetări Marine - Recherches Marines, 2026)
The authors present the results of malacological analyses of the samples taken from the surface of sediments and from a carrot in the zone of Viteaz canyon (east of Constantza). They conclude that there is a transporting submarine agent along the canyon, which can be a ground stream, a submarine sliding or a turbidity current.